The role of developmental stage specific programmes in infant acute lymphoblastic leukaemia - Ling, R (2024)
The MLL rearrangement which causes the poor prognosis of infant acute lymphoblastic leukemia (iALL) occurs before birth. Fetal haematopoietic stem and progenitor cells (HSPC) have different gene expression profiles to their postnatal counterparts. One such fetal specific oncogene, LIN28B is aberrantly expressed in a wide range of cancers, including many with putative fetal origins and in murine models specifies fetal-like lymphopoiesis.